Dapagliflozin lowers blood pressure in hypertensive and non-hypertensive patients with type 2 diabetes. (September 2015) - Sjöström, C David; Johansson, Peter; Ptaszynska, Agata; List, James; Johnsson, Eva
The effect of dapagliflozin on blood pressure was evaluated in non-hypertensive (<140 mm Hg) and hypertensive (⩾140 mm Hg) patients with type 2 diabetes mellitus. Data were pooled from 13 placebo-controlled studies. Patients received dapagliflozin 10 mg/day ( n  = 2360) or placebo ( n  = 2295) for up to 24 weeks. Dapagliflozin was associated with placebo-subtracted changes from baseline in systolic and diastolic blood pressures of −3.6 and −1.2 mm Hg, respectively, in hypertensive patients and −2.6 and −1.2 mm Hg, respectively, in non-hypertensive patients. At 24 weeks, a similar proportion of patients experienced measured orthostatic reactions with dapagliflozin versus placebo in hypertensive (6.1% and 6.6%, respectively) and non-hypertensive (4.0% and 4.2%) patients. No clinically relevant difference was observed between dapagliflozin and placebo in heart rate. In conclusion, dapagliflozin 10 mg induces a modest reduction in blood pressure compared with placebo in patients with diabetes with a low risk of orthostatic reactions, regardless of baseline blood pressure.